PEMBERDAYAAN EKONOMI ISLAM MELALUI OPTIMALISASI ZAKAT - Eko Haryono Eko Haryono (Al Fattah Ejournal Sma Al Muhammad Cepu, 2023)
Zakat, as an important instrument in the structure of moral and social and economic development, is the most important part of Islamic values regulated by Sharia. this study aims to describe, and analyze zakat in the perspective of islamic economics, zakat overcomes inequality and poverty, and islamic economic empowerment through zakat, while the approach used is descriptive and qualitative with the type of literature study research, the source of data used is Al Quran, books, articles and works related to the research focus. The results of the study are as follows: Islamic principles of economic empowerment of Muslims can be implemented through the process of realizing zakat. From an economic point of view, zakat should not be consumptive (short-term investment), but productive to increase the income level of Muslims and reduce poverty and social inequality. The ability to carry out the role of the government (amir) in zakat management is also very important and of course, must be accompanied by community management (supervision) so that there is no manipulation in the distribution of zakat